Commentary: Research Highlights (Neuronal Nicotinic Acetylcholine Receptors: Emerging Therapeutic Targets for Alcoholism) - Rahman, Shafiqur (CNS & Neurological Disorders - Drug Targets, 2011)
Alcoholism and alcohol use disorders (AUDs) impact millions of people and represent a significant global public health problem. According to the World Health Organization, alcoholism related deaths are estimated to account 3.2% of all deaths worldwide. Fetal alcohol syndrome, an important form of mental disability, caused by alcohol abuse and addiction by pregnant women, is on the rise. Previous research suggests that alcoholism is a progressive relapsing disorder of the brain and needs effective treatment to remain abstinent. Due to modest efficacy with currently approved medications, there is a need for new therapeutic strategies for the management of alcoholism. Evidence indicates that neuronal nicotinic acetylcholine receptors (nAChRs) are critical targets for the development of improved pharmacotherapies for alcoholism. However, it is not clear which subtypes of the neuronal nAChR are involved in alcoholism. Recent human genetic association studies have implicated the gene cluster CHRNA3-CHRNA5-CHRNB4 encoding the α3, α5, and β4 subunits of the nAChR in susceptibility to develop nicotine and alcohol dependence, indicating a potential role of these nAChR subunits. To examine the role of the α3 and β4 subunits of the nAChR in alcoholism, Chatterjee and colleagues have developed and characterized high-affinity partial agonists at α3β4 nAChRs, CP-601932, and PF-4575180 in preclinical models of alcoholism. The results suggest that both CP-601932 and PF- 4575180 selectively reduce alcohol but not sucrose self-administration, following long-term exposure. The authors also demonstrated that the functional potencies of CP-601932 and PF-4575180 at α3β4 nAChRs correlate with these compounds' unbound brain concentrations. These data indicate that the effects on alcohol self-administration are mediated by α3β4 nAChRs. Overall, the study suggests that α3β4 nAChRs could be critical therapeutic targets for the treatment of alcoholism and AUDs. In addition, the clinically safe novel partial nAChR agonist CP-601932 has the potential to reduce smoking in alcoholics with co-morbid nicotine dependence. This is due to similar affinity of the novel compound for α4β2 nAChRs that are involved in nicotine addiction. Future clinical studies in subjects with alcoholism and AUDs could further advance its development and use in humans.